Tantangan dan Prospek Penegakan Hukum Lingkungan di Indonesia - Tanjung, Rahmatan; Andini, Yola; Meisandi, Haikal; Dongoran, Nurmala Sari; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Environmental law enforcement in Indonesia continues to face complex challenges despite noticeable improvements in institutional capacity and regulatory frameworks. This study employs a literature-based research method to examine the dynamics, obstacles, and prospects of environmental law enforcement from various scholarly sources, government reports, and legal documents. Data from the Ministry of Environment and Forestry (KLHK) indicate that more than 900 environmental crime cases were handled in 2023, with a cumulative total of over 7,800 reports since the establishment of the enforcement directorate. However, the high number of cases reflects persistent structural issues, including weak inter-agency coordination, ineffective sanctions, limited action against corporate and intellectual actors, and slow judicial processes. The findings also highlight significant prospects for improvement through restorative justice approaches, the use of artificial intelligence and big data in monitoring, the application of multidoor law enforcement, and stronger community participation. Overall, this study concludes that Indonesia possesses the legal instruments and institutional potential needed to strengthen environmental protection.